Effect of meal timing on pharmacokinetics and pharmacodynamics of tegoprazan in healthy male volunteers - Deok Y. Yoon; Jung Sunwoo; Naree Shin; Ah R. Kim; Bongtae Kim; Geun S. Song; In‐Jin Jang; SeungHwan Lee (Wiley, 2021)
Abstract Tegoprazan, a novel potassium‐competitive acid blocker, is used to treat acid‐related diseases. However, there is no information on the pharmacokinetic (PK) and pharmacodynamic (PD) profiles of the marketed dosage of tegoprazan under various meal timings in a fed and fasted state. The study aimed to assess the effect of meal timing on PKs and PDs of tegoprazan 50 mg after a single administration in healthy male subjects. An open‐label, single‐dose, three‐treatment, three‐period crossover study was conducted. A total of 12 subjects were orally administered a single dose of tegoprazan 50 mg among various conditions: in a fasted state, at 30 min before or 30 min after a high‐fat meal. PK parameters were estimated by the noncompartmental method. Continuous 24‐h intragastric pH monitoring was done for PD analysis. The PKs and PDs of tegoprazan were compared among the various meal timings. Compared with the fasting condition, the PK profile of tegoprazan was similar when administered 30 min before a high‐fat meal; however, delayed absorption with similar systemic exposure was observed when administered 30 min after a high‐fat meal. The magnitude of acid suppression evaluated through the PD parameters increased when administered 30 min after a high‐fat meal compared with fasting the condition and when administered 30 min before a high‐fat meal. However, the increased difference in acid suppression was not clinically significant. Meal timing had no clinically significant effect on the PKs and PDs of tegoprazan 50 mg. Therefore, the marketed dosage of tegoprazan could be administered regardless of the meal timing. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? Tegoprazan, a novel potassium‐competitive acid blocker, is used to treat acid‐related diseases. WHAT QUESTION DID THIS STUDY ADDRESS? This study evaluated the effect of food on pharmacokinetics (PKs) and pharmacodynamics (PDs) of tegoprazan under various mealtime conditions. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? This study showed that delayed absorption of tegoprazan was observed at "after meal condition," however, the amount of systemic exposure of "after meal condition" was similar to "fasting condition" and "before meal condition." In addition, gastric acid suppression of tegoprazan was similar between fasting condition and before meal condition, whereas increased gastric acid suppression was observed at after meal condition. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? In the actual clinical environment, patients take medicine under various fed conditions. This study evaluated the effect of food on PKs and PDs of tegoprazan in various clinical conditions, and provided the important information about meal timing when administering tegoprazan.